Teachers’ Perception On Modular Distance Learning Approach At Mindanao State University-Sulu: Its Readiness And Challenges - Jayani, Padzmahal G. (HM Publisher, 2021)
This study aimed to know the “Teachers’ Perception on Modular Distance Learning Approach at Mindanao State University-Sulu: Its Readiness and Challenges”. This study contained five (5) objevtives:1) to determine the profile of the respondents; 2) to determine the perceptions of the teachers towards the modular distance learning approach; 3) to find out the challenges encountered by the teachers with modular distance learning approach; 4) to determine the level of readiness on modular distance learning approach as perceived by the teachers; and 5) to find out if there is a significant difference between perception of readiness and challenges in terms of age. This study is supported by Michael G. Moore’s Transactional Distance Theory developed by Daniel Bornt (completed August 22, 2011) and Constructivist Theory by Saul McLeod, published 2019. Moore’s theory has a direct bearing on e-learning. It explains and quantifies the learning relationship between instructor and student in the e-learning situation, where there is a substantial physical or temporal distance between the two. First formulated in 1997, it considered the many different forms of distance learning as part of a group which could similarly analyzed. Transactional distance as distinguished from physical or temporal distance – refers to the psychological or communicative space that separates instructor from learner in the transaction between them, occurring in the structured or planned learning situation (Moore, 1997, p.1) and the constructivist learning theory underpins a variety of student-centered teaching methods and techniques which contrast with traditional education, whereby knowledge is simply passively transmitted by teachers to students. This study used convenient sampling technique. This sampling is also known as availability sampling. There were forty eight (48) teachers who served as the respondents from different colleges and department of Mindanao State University-Sulu, they were chosen depending on their availability at school. To gather data the researcher used survey questionnaire or the descriptive survey method. The questionnaire is guided by the objectives of the study. It consist of twenty five (25) items. This research instrument helped the researcher to determine the readiness and challenges of teachers’ perception on modular distance learning approach at Mindanao State University-Sulu. When the questionnaire were collected, the researcher made tabulations of the gathered data and subjected them to analysis. SSPS was used in computing and analyzing the data. Frequency and standard deviation were used to analyze the SOP1 which were the profile of the respondents. Weighted arithmetic mean for the SOP 2, 3 and 4, then the one-way ANOVA for the SOP 5. Based on the findings of the study, the distribution of first category which is age starts in 30 below has the frequency of 26, 31-40 and 41 above have the same frequency of 11, second category which is gender; there are more female respondents with 31 while male respondents have a frequency of 17 and the third category which is college. 9 respondents were from College of Arts and Sciences, both 7 respondents were from College of Education and College of Agriculture. Similarly, 6 respondents were from College of Fisheries and Senior High school Department, College of Computer Studies has frequency of 5 and 4 respondents came from College of Public Affair and College of Public. The study also revealed that the respondents agreed on teacher’s perception on modular distance learning approach with its grand mean of 3.00 with a description of Moderately Agree. The respondents also agreed on the challenges encountered with modular distance learning approach with its grand mean of 3.97 and a description of Agree. The result also concluded that the respondents have high level of readiness on modular distance learning approach with its grand mean of 3.51 with a description of High Readiness. The data indicated that there is no significant difference between perceptions on the level of readiness when the data are grouped according to age. Thus, the data suggest that the null hypothesis is accepted. The data also indicated that there is no significant difference between the perceptions on the challenges encountered during modular distance learning approach when the data are grouped according to age. Thus, the data suggests that the null hypothesis is accepted.